The Disadvantaged Sufferer : A diachronic transitivity analysis of disability within tabletop roleplaying game rulebooks - Elmnäinen, Helena (My University, 2026)
Tabletop roleplaying games (TTRPGs) often include disabling impairments and narratives in their rulebooks, but they are at the same time social and cultural products of their time. This study investigates how nine popular TTRPG rulebooks represent disability and what kind of disabled identities the rules allow players to inhabit. The texts are analysed with transitivity analysis to examine how the authors view the experience of disability. In addition, the methods of critical discourse analysis are used to find out the underlying ideologies and social context. The TTRPG rulebooks were gathered from between years 2000-2025. The selected books had more than ten disability-related sentences, were well-known in TTRPG communities and were available to the researcher. The books were divided to three groups based on the decades they were from for diachronic comparison. The sentences were broken down to traditional clauses and analysed through transitivity analysis. The resulting participants were lastly categorized for easier analysis. The results indicated that earlier books focused disability representation to the character creation, where disability was a negative feature of the character that limited the gameplay. TTRPG books from the 2020s included disability representation in the setting of the TTRPG books and removed the negative label associated with creating disabled characters. In addition, assistive devices increased in frequency and seemed to take the place of disabled characters as limiting factors in gameplay. The direction of disability representation in TTRPG books is optimistic, but the subject could use further voices of disabled persons on the issue.
Keywords: tabletop roleplaying games; disability; systemic functional grammar; transitivity analysis